2007
DOI: 10.1016/j.ajog.2006.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive discontinuation: do side effects matter?

Abstract: Side effects are absent or mild among most OC users, but women with complaints are more likely to discontinue. Side effects are less important reasons for discontinuation than widely believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 10 publications
4
71
1
8
Order By: Relevance
“…Women discontinuing COC who do not want to become pregnant must start their new method of contraception immediately because of the proven quick return of fertility [6]. Oral contraceptive first-year discontinuation rates range from 18% to 60% [7]. Women rarely stop COC use because they want to switch to a fertility awareness-based method [8]; however, adverse effects or health concerns are often cited as the reason for discontinuation of hormonal contraceptives [9].…”
Section: Introductionmentioning
confidence: 99%
“…Women discontinuing COC who do not want to become pregnant must start their new method of contraception immediately because of the proven quick return of fertility [6]. Oral contraceptive first-year discontinuation rates range from 18% to 60% [7]. Women rarely stop COC use because they want to switch to a fertility awareness-based method [8]; however, adverse effects or health concerns are often cited as the reason for discontinuation of hormonal contraceptives [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus CHCs with lower rates of unscheduled bleeding may be more acceptable for women. In contrast, Westhoff et al (24) found that factors other than side effects may be associated with discontinuation of OCs. Although findings may be conflicting, results of all studies are relevant for clinicians and underscore the need to communicate regularly with patients and provide adequate counseling to ensure proper use of CHCs and identification of potential causes of patient dissatisfaction and discontinuation and to avoid unintended pregnancies and other health-related issues.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies, however, have reported that discontinuation rates vary across patient populations and that other factors, such as availability, accessibility, and acceptability, appear to influence continuation rates with CHCs. In a community-based, prospective study designed to assess self-reported sides effects and their relationship with discontinuation of OCs among young, first-time users of OCs with limited access to health services, Westhoff et al (24) reported that access to pharmacy when pill supplies were exhausted is a major reason for patient nonadherence among the women who were surveyed; however, this survey did not include questions about bleeding as a cause of discontinuation.…”
mentioning
confidence: 96%
“…An individual who began oral contraceptives 1 day before a study visit would presumably be considered a ''current user,'' whereas someone who had discontinued her OC yesterday, or perhaps had just missed a pill on the day of the study visit, might not be considered a ''current user.'' Many adolescents have difficulty with consistent pill use; one report found that adolescents who were ongoing OC users missed an average of three pills per month [7][8][9]. It might have been useful for the authors to analyze for ''ever-use'' of OCs or other hormonal contraception.…”
mentioning
confidence: 95%